Application of SEBAL methodology for estimating and disseminating through 3rd generation mobile phones crop water requirements in Cyprus - Papadavid, George; Hadjimitsis, Michael; Perdikou, Skevi; Hadjimitsis, Diofantos G.; Papadavid, C.; Neophytou, N.; Kountios, Georgios; Michaelides, Anastasios (My University, 2013)
Water allocation to crops has always been of great importance in agricultural process. In this context, and under the current conditions, where Cyprus is facing a severe drought from time to time, purpose of this study is basically to estimate the needed crop water requirements for supporting irrigation management and monitoring irrigation on a systematic basis for Cyprus using remote sensing techniques. The use of satellite images supported by ground measurements has provided quite accurate results. Intended purpose of this paper is to estimate the Evapotranspiration (ET) of specific crops which is the basis for irrigation scheduling and establish a procedure for monitoring and managing irrigation water over Cyprus, using remotely sensed data from Landsat TM/ ETM+ and a sound methodology used worldwide, the Surface Energy Balance Algorithm for Land (SEBAL). Finally Crop Water Requirements derived from the specific research are disseminated to crop producers through a network of 3rd generation mobile phones.
Keywords: Agricultural process; Crop water requirements; Ground measurements; Irrigation management; Irrigation scheduling; Remote sensing techniques; Remotely sensed data